Participation in Physical Activity and Physical Education in School Among Children With Acute Lymphoblastic Leukemia After Intensive Chemotherapy - Alias, Hamidah; Mohd Nazi, Nur Adlina; Lau Sie Chong, Doris (Frontiers in Pediatrics, 2019)
Background: Low physical activity (PA) level has been reported among survivors of childhood acute lymphoblastic leukemia (ALL). The present study was performed to determine the level of participation in general PA and physical education in school (PES) among children with ALL who completed intensive chemotherapy and identify possible barriers that influence adherence to PA and PES. Methods: A cross-sectional, single-center study was conducted over 1 year in a tertiary pediatric hematology and oncology referral center in Kuala Lumpur, Malaysia. A total of 47 children with ALL aged 7–18 years old who were off-treatment and attended school on a regular basis were recruited. A modified structured questionnaire adapted from the Youth Risk Behavior Surveillance System, Division of Adolescent and School Health, the Centers for Disease Control and Prevention (CDC) was used to assess the children’s level of PA and PES participation. Results: Among the 47 children will ALL included herein, 11 (23.4%) were physically active for at least 60 min a day for 5 days or more, following CDC recommendations. The median duration from completion of intensive chemotherapy was 4.95 years (25th, 3.29; 75th, 7.95). Younger age at study entry (median, 8.7 years old vs. 12.2 years old) and younger age at diagnosis (median, 2.9 years old vs. 4.3 years old) were significantly associated with higher PA level. Almost all children (45/47, 95.7%) participated in PES. Barriers to non-participation in PES mainly included exhaustion or fear of injury. Conclusions: Majority of the children with ALL included herein had low levels of daily PA after intensive chemotherapy. Nonetheless, their participation in PES was encouraging. PA should thus be promoted during and after cessation of ALL treatment to prevent long-term health risks and improve overall quality of life.